2008
DOI: 10.1143/jpsjs.77sa.315
|View full text |Cite
|
Sign up to set email alerts
|

Optical Conductivity and Electronic Structures in Ce-Filled Skutterudites

Abstract: Optical conductivity [σ(ω)] spectra have been measured for eight Ce-filled skutterudite compounds CeT4X12 (T =Fe, Ru, Os; X=P, As, Sb) to systematically study their microscopic electronic structures around Fermi level. The σ(ω) spectra show large differences among X=P, As and Sb, while they show smaller differences among T =Fe, Ru and Os for a given X element. This indicates that the choice of X has larger effects on the electronic structures of CeT4X12 than that of T . The spectral shape and temperature depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[In the case of CeX 4 P 12 (X=Fe, Ru, Os), 38) an energy gap with an onset at 0.2-0.3 eV was actually observed ] To explain the above result and the metallic characteristics observed in other physical properties, we suggest that the actual band structure should be similar to that described in Fig. 7(b).…”
Section: Electronic Structures Of Cerumentioning
confidence: 64%
See 1 more Smart Citation
“…[In the case of CeX 4 P 12 (X=Fe, Ru, Os), 38) an energy gap with an onset at 0.2-0.3 eV was actually observed ] To explain the above result and the metallic characteristics observed in other physical properties, we suggest that the actual band structure should be similar to that described in Fig. 7(b).…”
Section: Electronic Structures Of Cerumentioning
confidence: 64%
“…Note that in CeM 4 P 12 and CeM 4 As 12 , whose lattice constants are smaller than that of CeM 4 Sb 12 , an energy gap is in fact observed. [6][7][8][9][10]38)…”
Section: Electronic Structures Of Cerumentioning
confidence: 99%
“…The extracted DOS(E F ) of CeFe 4 P 12 thus reveals a V-type depletion of spectral weight within ∼110 meV of E F , and E F would be centred at the middle of the gap. While an early optical spectroscopy study of the material reported a gap size of about 150 meV [45], a recent study has shown a gap of 0.22-0.24 eV [23]. Thus, UPS is measuring roughly half the gap seen in optical spectroscopy.…”
Section: Resultsmentioning
confidence: 95%
“…However, the Hall coefficient for CeFe 4 P 12 is positive between 25 and 300 K and increases with decreasing temperature, thus suggesting that the dominant carriers are holes and its concentration decreases with decreasing temperature [17]. An optical gap of about 0.22-0.24 eV has been reported recently for single crystal CeFe 4 P 12 [23]. Also, the magnetic susceptibility below room temperature shows a continuous decrease in the effective magnetic moment for CeFe 4 P 12 [22].…”
Section: Introductionmentioning
confidence: 88%